Progress on Genetic Improvement and Analysis of Bottle Gourd [Lagenaria siceraria (Molina) Standl.] for Agronomic Traits, Nutrient Compositions, and Stress Tolerance: A Review - Mkhize, Phumzile; Mashilo, Jacob; Shimelis, Hussein (Frontiers in Sustainable Food Systems, 2021)
Bottle gourd [Lagenaria siceraria (Molina) Standl.] is an important multi-purpose cucurbit crop grown for its leaf, fruit and seed. It is widely cultivated and used for human consumption in sub-Saharan Africa (SSA) providing vital human nutrition and serving as food security crop. There is wide genetic variation among bottle gourd genetic resources in Africa for diverse qualitative and quantitative attributes for effective variety design, product development and marketing. However, the crop is under- researched and -utilised, and improved varieties are yet to be developed and commercialized in the region. Therefore, the objective of this review is to provide the progress on bottle gourd genetic improvement and genetic analysis targeting agronomic and horticultural attributes, nutritional composition, biotic and abiotic stress tolerance to guide current and future cultivar development, germplasm access and conservation in SSA. The first section of the paper presents progress on breeding of bottle gourd for horticultural traits, agronomic performance, nutritional and anti-nutritional composition, and biotic and abiotic stress tolerance. This is followed by important highlights on key genetic resources of cultivated and wild bottle gourd for demand driven breeding. Lastly, the review summaries advances in bottle gourd genomics, genetic engineering and genome editing. Information presented in this paper should aid bottle gourd breeders and agronomists to develop and deploy new generation and promising varieties with farmer- and market -preferred attributes.